Haematological Profile of Adults with Malaria Parasitaemia Visiting the Volta Regional Hospital, Ghana - Daniel Sakzabre; Emmanuel Akomanin Asiamah; Elliot Elikplim Akorsu; Albert Abaka-Yawson; Noble Dei Dika; David Annor Kwasie; Emmanuel Ativi; Confidence Tseyiboe; George Yiadom Osei (Advances in Hematology)
Background. Malaria is known to cause severe health consequences due to its marked effects and alteration on the haematological parameters of infected individuals. This study evaluated the haematological profile of adult individuals infected with the malaria parasite. Methods. A retrospective study was conducted using archived data of malaria positive cases from January 2017 to March 15, 2019. Data retrieved included subjects’ demographics, malaria parasite count, malaria parasite species, and full blood count parameters. A total of 236 malaria positive subjects were included in the study. Results. The study showed that more females were infected with the malaria parasite than males (69.07% and 30.93%, respectively). A total of 87.3% of the study population were infected with Plasmodium falciparum as compared to 12.7% infected with Plasmodium malariae. The commonest haematological abnormalities that were seen in this study were lymphopenia (56.78%), anaemia (55.51%), thrombocytopenia (47.46%), eosinopenia (45.76%), neutropenia (29.24%), monocytosis (21.19%), and leucocytosis (17.37%) in the infected subjects. The mean platelet count of P. falciparum-infected subjects was decreased as compared to the mean platelet count of P. malariae-infected subjects. There was a significant (P value <0.05) decrease in the number of platelet count with every unit increase in parasite density. Conclusion. Study participants infected with malaria demonstrated vital changes in haematological parameters with anaemia, thrombocytopenia, lymphopenia, monocytosis, and eosinopenia being the most important predictors of malaria infection especially with P. falciparum species.